STRUCTURE, AGE AND MODE OF EMPLACEMENT OF THE HERCYNIAN BORDèRES-LOURON PLUTON (CENTRAL PYRENEES, FRANCE) - Gleizes G.; Crevon G.; Asrat A.; Barbey P. (My University, 2006)
The Hercynian Bordères-Louron pluton (20 km2) in the Central Pyrenees intrudes Devonian and Carboniferous metasediments. It shows a concentric zoning and consists of a significant proportion of (quartz) gabbros in its periphery, and of granodiorites, biotite monzogranites and biotite-muscovite monzogranites in its core. AMS study shows that the pluton corresponds to an elongated dome with a N100°E-trending axis. The anisotropy intensity Ppara% is high in the south and in the core of the pluton, whereas it is low in the north. The shape parameter T indicates that the fabric is strongly planar in a large central band oriented NW-SE, whereas it is strongly linear in the western and eastern tips of the pluton. These characteristics suggest that the Bordères-Louron pluton emplaced in two episodes: (1) intrusion of mafic magmas along a N100°E sill parallel to the regional foliation of the host metasediments; and (2) injection of three successive silicic batches (granodiorite, biotite monzogranite, two-micas monzogranite) which pushed aside the early mafic injections. In situ U-Pb dating of zircon grains indicates that the emplacement age of the biotite monzogranite is 309 ± 4 Ma, synchronous with the D 2 dextral transpressive event and close to the ages of the eastern Pyrenean plutons, may be slightly older.
Keywords: GRANITE EMPLACEMENT; VARISCAN PYRENEES; ZIRCON U-PB AGE; ANISOTROPY OF MAGNETIC SUSCEPTIBILITY; BORDèRES-LOURON; Carboniferous; Devonian; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская